Synthesis, Characterization, Semiempirical and Biological Activities of Organotin(IV) Carboxylates with 4-Piperidinecarboxylic Acid - Shabbir Hussain; Saqib Ali; Saira Shahzadi; Saroj K. Sharma; Kushal Qanungo; Muhammad Shahid (Bioinorganic Chemistry and Applications)
Organotin (IV) carboxylates with the general formulae R2Sn(Cl)L [R = Me (1), n-Bu (2), Ph (3)] and R3SnL [R = Me (4), Ph (5)] have been synthesized by the reaction of 4-piperidinecarboxylic acid (HL) with KOH and R2SnCl2 (R = Me, n-Bu, Ph)/R3SnCl (R = Me, Ph) in methanol under stirring conditions. The metal ligand binding site, structure, and stability of complexes have been verified by FT-IR, (1H, 13C) NMR, EI-MS technique, and semiempirical study. The FT-IR data indicate the bidentate chelating mode of the carboxylate ligand which is also confirmed by semiempirical study. In solution state, five and four coordinated geometry around tin was confirmed by NMR spectroscopy. The EI-MS data agreed well with the molecular structure of the complexes. Thermodynamic parameters and molecular descriptors were calculated by using semiempirical PM3 method. HOMO-LUMO calculations show that chlorodiorganotin complexes are more susceptible to nucleophilic attack as compared to triorganotin complexes. Computed negative heat of formation indicates that complexes 1–4 are thermodynamically stable. The organotin(IV) carboxylates displayed powerful antimicrobial activities against various strains of bacteria and fungi and their minimal inhibitory concentration were also evaluated. The complexes exhibited comparatively higher hemolytic activity as compared to free ligand.